On dark optical solitons of the space-time nonlinear Schrodinger equation with fractional complex transform for Kerr and power law nonlinearities - Yusuf, Abdullahi; İnç, Mustafa; Aliyu, Aliyu Isa (Amer Scientific Publishers, 2018)
This paper presents an investigation of the space-time nonlinear Schrodinger equation (NLSE) involving Kerr and power law nonlinearity with local fractional (LF) calculus. The powerful tanh method (TM) with the aid of fractional complex transform is applied to extract novel dark optical solitons for the governing equation. The obtained results have been visualized and discussed in detail.
Keywords: Nonlinear Schrodinger Equation; Local Fractional Derivative; Dark Optical Solitons; Negative-Index Materials